2004
DOI: 10.1111/j.0001-5172.2004.00385.x
|View full text |Cite
|
Sign up to set email alerts
|

Olprinone improves diaphragmatic contractility and fatigability during abdominal sepsis in a rat model

Abstract: Olprinone represents a potential therapy for cases of respiratory failure with diaphragmatic fatigability resulting from inhibition of neutrophil activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 19 publications
2
7
0
2
Order By: Relevance
“…Since in septic patients cAMP stores were found depleted (54), the authors also speculated that phosphodiesterase inhibition would alleviate fatigue patterns. Using the PDE inhibitor olprinone, both MPO activity and fatigue were restored similarly towards control levels, indicating a crucial involvement of activated neutrophils or macrophages within septic tissue to contribute to downstream muscle weakness and increased fatigability, probably through their cytokine release patterns of IL-1 and TNF-␣ or free radicals (94,224,488). In chronic inflammatory conditions of polymyositis and dermatomyositis, muscle weakness in patients was correlated with a strong expression of IL-1␣ in patient muscle tissues (516).…”
Section: E Muscle Fatigue In Critical Illnessmentioning
confidence: 94%
See 1 more Smart Citation
“…Since in septic patients cAMP stores were found depleted (54), the authors also speculated that phosphodiesterase inhibition would alleviate fatigue patterns. Using the PDE inhibitor olprinone, both MPO activity and fatigue were restored similarly towards control levels, indicating a crucial involvement of activated neutrophils or macrophages within septic tissue to contribute to downstream muscle weakness and increased fatigability, probably through their cytokine release patterns of IL-1 and TNF-␣ or free radicals (94,224,488). In chronic inflammatory conditions of polymyositis and dermatomyositis, muscle weakness in patients was correlated with a strong expression of IL-1␣ in patient muscle tissues (516).…”
Section: E Muscle Fatigue In Critical Illnessmentioning
confidence: 94%
“…Trains of tetanic stimulations (50 Hz for 2 s every 10 s for 5 min) were applied. Times to half decrement of the first peak tetanic tension (T 50 ) as fatigability index revealed an almost 50% shorter T 50 indicative of massive fatigue (488). This fatigue was associated with a marked increase in myeloperoxidase activity (MPO) as an index of neutrophil activation in septic muscle tissue.…”
Section: E Muscle Fatigue In Critical Illnessmentioning
confidence: 99%
“…Therefore, we have focused on neutrophil migration and activation associated with organ dysfunction in septic rats. Our previous study showed that the degree of diaphragmatic fatigability paralleled MPO activity in the diaphragm [7]. This suggests that neutrophil activation is essential for the development of diaphragmatic fatigability.…”
Section: Discussionmentioning
confidence: 81%
“…It has been suggested that the diaphragmatic fatigability associated with abdominal sepsis is induced by activated neutrophils in diaphragmatic muscle in which myeloperoxidase (MPO) activity is increased [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation